Incorporating therapeutic drug monitoring into the World Health Organization hierarchy of tuberculosis diagnostics. Issue 6 (17th March 2016) - Ghimire, Samiksha; Bolhuis, Mathieu S.; Sturkenboom, Marieke G.G.; Akkerman, Onno W.; de Lange, Wiel C.M.; van der Werf, Tjip S.; Alffenaar, Jan-Willem C.
Tuberculosis (TB), once considered as a disease of the past generally afflicting poor people, still claims 1.5 million lives annually [1]. Although 86% of patients with drug susceptible TB are cured with established first-line drugs, treatment is often longer than 6 months due to slow response, compliance problems or adverse drug reactions. In addition, emergence of drug-resistant Mycobacterium tuberculosis strains with an unacceptably low treatment success rate of 50% and TB–HIV co-infection have challenged the goals of global TB control and elimination [1]. Incorporating therapeutic drug monitoring into the WHO hierarchy of tuberculosis diagnostics http://ow.ly/YcRMw